Perilaku Masyarakat dan Lingkungan dengan Kejadian Malaria di Puskesmas Arso Kota - Rohmani Rohmani; Zeth Robert Felle; Frengky Apay (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Malaria remains a significant public health issue both globally and in Indonesia, particularly affecting high-risk groups such as infants, young children, and pregnant women. The increasing incidence of malaria is closely linked to environmental and behavioral factors. This study aims to examine the relationship between community behavior and environmental conditions with malaria incidence at the Arso City Health Center, Keerom Regency. A quantitative, cross-sectional design was used, allowing analysis of variables at a single point in time. The sample was selected through simple random sampling based on inclusion and exclusion criteria. Findings revealed that there is no significant relationship between the habit of going outside the house and malaria incidence (p = 0.07). However, there is a significant relationship between the use of mosquito repellent and malaria incidence (p = 0.000). Similarly, using mosquito nets and gauze also showed a significant relationship with reduced malaria cases. Environmental aspects such as mosquito breeding sites and unsealed house walls were also found to be significantly associated with malaria occurrence. These results suggest that both behavioral factors—particularly protective measures—and environmental conditions contribute to malaria transmission in the community. Public health efforts should prioritize education on preventive behaviors and improvements in living environments to reduce malaria risk.